Synergy Of Ethical Leadership And HPWS: Unveiling Employee Motivation And Performance In Public Sector - Khairuddin Safa'at; Aryana Satrya (UNIVED Press, 2025)
This study empirically explores the improvement of job performance in the public sector through an approach that combines aspects of leadership with ethical leadership, a system aspect approach with a High-Performance Work System (HPWS), and an individual aspect approach with employee motivation within the scope of government financial institutions (GFI). Social Exchange Theory is used as a conceptual basis. Data were collected through an online questionnaire with a 7-point Likert scale measurement. The analysis was carried out using the Structural Equation Modeling (SEM) technique with SmartPLS 4 software to test the combination of multidimensional and unidimensional variables. The data obtained were 843 and after going through the screening and data cleaning process, 640 respondent responses were obtained for testing. The results of the study indicate that ethical leadership and HPWS have a positive and significant effect on employee motivation and job performance, and employee motivation has a positive and significant effect on job performance. In addition, employee motivation mediates positively and partially the relationship between ethical leadership and HPWS on job performance. This study provides theoretical contributions by combining ethical leadership and HPWS perspectives in one model that explains how these two factors affect job performance in the public sector through employee motivation mediation, while adding employee motivation as an intermediary mechanism to improve job performance in the public sector.